Cardiopulmonary Exercise Testing in Patients With Left Bundle Branch Block and Preserved Ejection Fraction - Barros,Milena dos Santos (2017)
Abstract Background: Left bundle branch block (LBBB) has prognostic significance in patients with congestive heart failure. However, its influence is not well established in patients with preserved systolic ventricular function. Objective: To evaluate the implications of LBBB presence in the cardiovascular performance of patients with preserved left ventricular systolic function (LVEF). Methods: 26 LBBB patients (61.3 ± 8.2 years of age) and 23 healthy individuals (58 ± 6.8 years of age) with LVEF > 0.5 underwent cardiopulmonary exercise testing (CPET). Results: CPET analysis revealed: peak oxygen consumption (VO2) predicted in the LBBB group was 87.2 ± 15.0% versus 105.0 ± 15.6% (p < 0.0001); peak oxygen pulse predicted in LBBB group was 98.6 ± 18.6% vs 109.9 ± 13.5% (p = 0.02); VO2 predicted anaerobic threshold in LBBB group was 67.9 ± 13.6% vs 70.2 ± 12.8% (p = 0.55); ΔVO2/Δload in the LBBB group was 15.5 ± 5.51 versus 20.7 ± 7.3 ml.min-1.watts-1 (p = 0.006); ventilation / carbon dioxide production (VE/VCO2 slope) in LBBB group was 29.8 ± 2.9 versus 26.2 ± 2.9 (p = 0.0001) and VO2 recovery time in the LBBB group was 85.2 ± 11.8 vs. 71.5 ± 11.0 seconds (p = 0.0001). LBBB was an independent marker for VE/VCO2 slope increase. Conclusion: LBBB presence in individuals with preserved LVEF did not affect cardiovascular performance, but there was an increase of the VE/VCO2 slope in comparison to the control group.